Civil disorder and insecurity within Fiji : an analysis of causes, effects, and an argument for future New Zealand strategic policy : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Defence and Strategic Studies at Massey University, Manawatu, New Zealand - Neal, David John (Massey University, 2012)
The thesis provides an analysis of the causes and effects of civil disorder and internal insecurity within Fiji. By understanding these influences, and New Zealand‟s desired strategic endgame in regards to the future of Fiji, an argument will be provided for strategic policy that New Zealand may pursue in regards to future interface with Fiji. While each particular coup and mutiny that has occurred within Fiji in recent history has been widely documented, a comprehensive analysis of the causes of each incident has not. The thesis examines the importance of Fiji to New Zealand (and Australia), and leads the reader through an analysis of race relations, history and culture as a means to expose some of the contributing factors regarding civil disorder and insecurity in Fiji. The thesis then progresses to examine the series of coups and mutiny that have occurred between the period of 1987 and 2006, prior to analyzing possible risks and consequences that may result from the current political situation in Fiji. The thesis will conclude with an argument for New Zealand‟s recommended policy towards Fiji that will help to achieve New Zealand‟s desired strategic endgame in regards to the future relationship with that nation. Fiji is not a failed state however, as a nation it is in a position of economic and political degradation, while the current attitude, capability and direction of the Republic of Fiji Military Forces (RFMF) is also of some concern. Fiji has become isolated from traditional allies such as New Zealand and Australia and now looks to some larger Asian nations for support under Commodore Bainimarama‟s „Look North‟ Policy. The future of strategic affairs and international relations that may result from the current situation in Fiji does create some potential risks within the South Pacific region, not to mention the future economy and standard of living for the population of Fiji. Given the current situation, and a proposed future democratic election in 2014, Fiji sits at a political cross-road. The current militarisation of the Fiji Government is not ethical and the result of Bainimarama's planned general election is yet to be determined. However, once Fiji has irreversibly committed to pursuing democracy, New Zealand should seize the opportunity to decisively and comprehensively renew links with Fiji. Options for this engagement include a progressive, whole of government approach utilising prudent application of all of the instruments of national power in an integrated manner.
Keywords: Fiji; Military coups, Fiji; Coups d'état, Fiji; Military history, Fiji; New Zealand strategic policy; New Zealand relations with Fiji